Ditadura civil-militar em livros didáticos de história: uma análise de gêneros textuais na perspectiva sistêmico-funcional da linguagem - Weber, Sabrine (2019)
The objective of this paper is to investigate the textual genres of the histories family and their purposes in History textbooks referring to the curricular content of Civic-Military Dictatorship. In this study, theoretical bases of the Systemic-Functional Linguistics are used (HALLIDAY; MATTHIESSEN, 2014). The analysis has as its starting point the characteristics of the family of history genres already mapped by Coffin (2006; 2008), Martin and Rose (2008), Christie and Derewianka (2008). The texts are analyzed from the most salient semantic-discursive systems of this family of genres: Ideation, Appraisal and Conjunction (MARTIN; ROSE, 2007). As the universe of analysis, the 9th grade textbook "História: Sociedade & Cidadania" (BOULOS, 2015), from FTD publisher, was selected since it is the most distributed book by PNLD (Brazilian Textbook Program) in the triennium 2017-2019 for public schools in Brazil. There are 10 texts in this research that, after the analysis, have revealed to be part of the family history genres. The analysis of the semantic-discursive systems, which contribute to the achievement of the genre stages in each text, evidenced two instances of the historical recount genre, whose predominant linguistic characteristics were precise circumstances and conjunctions of time and temporal relations between events; and eight instantiations of the historical account genre, whose predominant linguistic characteristics were relational processes in the Background stage, and material processes in the Account stage, besides presenting a relation of cause, consequence and addition between events. These events are articulated, in historical account, by means of six sequential explanations, two by means of consequential explanations and one by means of factorial explanation. The textbook’s chapter was identified as a macrogenre, a study of the period, which presents, in the analyzed corpus, a description of the period through a relation of extension among the textual genres identified in order to explain the Civic-Military Dictatorship content.